The border captains [large type] - Manning, Jason (Flintlock, 2022)
"The Revolutionary War is over and the fledgling United States is struggling to survive. With the turn of a new century, settlers are poised to continue their westward move through the dark and bloody killing grounds of Kentucky. In their path stand the British military's might and an even more menacing foe-the brave and brilliant Shawnee war leader, Tecumseh. Now the War of 1812 is about to break out, and the future of the new republic rests in the hands of American heroes like "Mad" Anthony Wayne, William Henry Harrison, the trigger fingers of a buckskin-clad army of undaunted conscripts, and in the courage, daring and determination of frontiersman Nathaniel "Flintlock" Jones. History is to be made, a wilderness to be won, and a spellbinding saga of the early American frontier is to be brought to pulse-pounding, unforgettable life. THE BORDER CAPTAINS IS THE SECOND EPIC HISTORICAL NOVEL OF THE FLINTLOCK TRILOGY BY THE ACCLAIMED AUTHOR OF THE HIGH COUNTRY SERIES"--